Professional Accounting Education in Indonesia: Evidence on Competence and Professional Commitment - Utami, Wiwik; Priantara, Diaz; Manshur, Tubagus (Asian Journal of Business and Accounting, 2017)
This study aims at examining whether accounting graduates who have achieved the Professional Accounting Education (PAE) certification possess a higher competency level compared to those who do not yet have PAE certification The study also examines whether those who possess a PAE certificate have better commitment to their career as public accountants than their counterparts who do not possess PAE certificates. The population of this study consists of auditors or accountants who work in public accounting firms in Jakarta. The population is divided into two sub populations consisting of junior auditors and senior auditors (supervisor, manager and partner). The sample of each sub population was selected using the ‘judgmental’ method. In order to examine the competency and commitment of junior auditors who had passed the PAE, we used case studies to test them; while questionnaires were used to obtain the perceptions of senior auditors regarding the competency and commitment of junior auditors. The findings reveal that the competency and commitment of junior auditors who possess PAE certificates are significantly higher than those with no PAE certification. This implies that PAE has made accountants or auditors more professional, suggesting that auditors ought to possess PAE certification. Keywords: Professional Accounting Education, Commitment, Competency, Professional Accountant